What are the benefits and risks of nutrition policy actions to reduce added sugar consumption? An Australian case study. Issue 7 (24th July 2022) - Russell, Cherie; Baker, Phillip; Grimes, Carley; Lawrence, Mark Andrew
Abstract: Objective: This study aimed to critically analyse Australia's current and proposed policy actions to reduce added sugar consumption. Over-consumption of added sugar is a significant public health nutrition issue. The competing interests, values and beliefs among stakeholders mean they have disparate views regarding which policy actions are preferable to reduce added sugar consumption. Design: Semi-structured interviews using purposive, snowball sampling and policy mapping. Policy actions were classified by two frameworks: NOURISHING (e.g. behaviour change communication, food environment and food system) and the Orders of Change (e.g. first order: technical adjustments, second order: reforming the system, third order: transforming the system). Setting: Australia. Participants: Twenty-two stakeholders from the food industry, food regulation, government, public health groups and academia. Results: All proposed and existing policy actions targeted the food environment/behaviour change; most were assessed as first-order changes, and reductionist (nutrient specific) in nature. Influences on policy actions included industry power, stakeholder fragmentation, government ideology/political will and public pressure. Few stakeholders considered potential risks of policy actions, particularly of non-nutritive sweetener substitution or opportunity costs for other policies. Conclusions: Most of Australia's policy actions to reduce added sugar consumption are reductionist. Preferencing nutrient specific, first-order policy actions could reflect the influence of vested interests, a historically dominant reductionist orientation to nutrition science and policy, and the perceived difficulty of pursuing second- or third-order changes. Pursuing only first-order policy actions could lead to 'regrettable' substitutions and creates an opportunity cost for more comprehensive policy aimed at adjusting the broader food system.